Open Heart Surgery In Octogenarian Patients: A Comparison Of Two Eras - Mehmet Erdem Toker; Gürkan Ayaz; Veysel Başar; Ayhan Güneş (Genel Tıp Dergisi)
Aim: In this study, it was aimed to compare two different periods in terms of surgical results in octogenarian patients who underwent open heart surgery.